2014
DOI: 10.6026/97320630010647
|View full text |Cite
|
Sign up to set email alerts
|

Differences in protein-protein association networks for lung adenocarcinoma: A retrospective study

Abstract: Various methods to determine the connectivity scores between groups of proteins associated with lung adenocarcinoma are examined. Proteins act together to perform a wide range of functions within biological processes. Hence, identification of key proteins and their interactions within protein networks can provide invaluable information on disease mechanisms. Differential network analysis provides a means of identifying differences in the interactions among proteins between two networks. We use connectivity sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
2
0
0
Order By: Relevance
“…The dominant network features in tumors of this cluster were formed by the proteins c-Met, ERCC1, Caspase-8, Snail, PARP, and RB. This expands the results of Datta et al who described this regulatory pattern for LUAD using a partial least squares method 40 . The largest regulatory network they found included ERCC1, PARP, Snail, c-Met, Caspase-8, and Rb, but connections to RB were reduced in a subgroup that showed tumor progression.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The dominant network features in tumors of this cluster were formed by the proteins c-Met, ERCC1, Caspase-8, Snail, PARP, and RB. This expands the results of Datta et al who described this regulatory pattern for LUAD using a partial least squares method 40 . The largest regulatory network they found included ERCC1, PARP, Snail, c-Met, Caspase-8, and Rb, but connections to RB were reduced in a subgroup that showed tumor progression.…”
Section: Discussionsupporting
confidence: 84%
“…The most important network features were the proteins PARP, Caspase-8, Snail, c-Met, ERCC1, and RB. Importantly, these predicted network patterns that appear to be highly conserved across these samples have also been reported in a study that examined protein regulation in a cohort of LUAD (see also discussion) 40 . Further analysis showed that the inferred interaction strength between these proteins had a bimodal distribution in cancers of the gastrointestinal tract, the lung, and the uterus while LRP scores for other tumors only were distributed around the lower peak (see Supplementary Fig.…”
Section: Resultssupporting
confidence: 64%